2022
DOI: 10.1007/s00431-022-04377-z
|View full text |Cite
|
Sign up to set email alerts
|

Multisystem inflammatory syndrome in neonates (MIS-N) associated with SARS-CoV2 infection: a case series

Abstract: Multisystem inflammatory syndrome in neonates (MIS-N) is hypothesised to be caused either following transplacental transfer of SARS-CoV2 antibodies or antibodies developed in the neonate after infection with SARS-CoV-2. In this paper, we aim to discuss the clinical manifestations, laboratory features, and management of neonates diagnosed with MIS-N. We collated information from five participating hospitals in western India. A cohort of newborn infants presenting with multi-system involvement, along with the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 36 publications
2
58
0
1
Order By: Relevance
“…2. Late MIS-N − hypothesized as occurring due to antibodies produced secondarily to SARS-CoV-2 infection in the newborn when the neonate presents with clinical and laboratory features beyond the first 72 h of age [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2. Late MIS-N − hypothesized as occurring due to antibodies produced secondarily to SARS-CoV-2 infection in the newborn when the neonate presents with clinical and laboratory features beyond the first 72 h of age [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Demographic, clinical presentation, length of the hospital stay, and outcome of neonates with MIS-N[4,5,14,[16][17][18][19][20][21][22][23][24][25][26][27][28] …”
mentioning
confidence: 99%
“…On January 18, 2022, more than 50 cases of MIS-N have been described (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). As in older infants and children, the lack of a diagnostic test makes the clinical diagnosis challenging in non specific cases.…”
Section: Prompt Recognition Of Mis-nmentioning
confidence: 99%
“…In this study, it was shown that some inflammatory tests of even asymptomatic infants born to mothers with infections and who did not require intensive care follow-up differed from those of healthy infants born to COVID-19 PCR negative mothers. Although there is no detailed study in the literature about the period of postnatal life until when this difference may last, in a study by More et al 27 in which 20 MIS-N cases were included, the SARS-CoV-2 IgG levels were found to be high, but the antigen levels were negative and it was shown that MIS-N condition might develop in case babies born to mothers with COVID-19 disease encountered the SARS-CoV-2 virus. In line with this information, it can be thought that inflammatory indices may be useful in the prediction of MIS-N and in the follow-up of treatment.…”
Section: Study Limitationsmentioning
confidence: 99%